Sosialisasi Penanaman Singkong di Pekarangan Rumah sebagai Wujud Pemanfaatan Ketersediaan Pangan Berkelanjutan di Kampung Pekijing, Kelurahan Kalang Anyar, Kota Serang - Muhammad Ilham Al Mubarok; Nia Adelia; Rayhan Kurnia; Citra Indah Pratiwi; Husnawati Husnawati; Lenggana Faiza Nugraha; Fitrianingsih Fitrianingsih; Muhammad Bayu Arya Dita; Dea Yohana Manik; Muhammad Ferryl Irawan; Annisa Annisa; Nurhasna Ayunda Sfitri (Universitas 45 Surabaya, 2025)
Food availability is one of the key indicators in achieving sustainable household food security. This community service activity was conducted in Kampung Pekijing, Kalang Anyar Subdistrict, with the aim of increasing public awareness and understanding of the importance of utilizing home yards for cassava (Manihot esculenta) cultivation as a practical effort to support local food availability. The method included educational outreach, participatory discussions, and the administration of pre-test and post-test questionnaires to 40 respondents. The results showed a significant improvement in the community's knowledge regarding the nutritional and economic benefits of cassava. A total of 100% of respondents expressed interest in reducing their dependence on rice, while 97.5% felt motivated to plant cassava in their home yards. The negative stigma that perceives cassava as a low-nutrient food decreased markedly from 52.5% to 12.5% after the session. These findings indicate that direct and contextual education effectively enhances community readiness to support food availability using accessible local resources. This program contributes positively to the development of community-based food security in an independent and sustainable manner.